Institutional Development in Public Transport Policy: A Literature Review - Thuang, Kwan Hue (Journal of Asian Multicultural Research for Social Sciences Study, 2020)
This article discusses institutional development in public transport policy in terms of concepts and theories. The institutionalized organization must establish and maintain a network in its environment to keep it alive and functioning, by adjusting to the relationships in an organization's life. The development of the transportation system is carried out in a sustainable, consistent, and integrated manner, both inter and between modes, with other development sectors and taking into account the existence of the local government. The policies formulated by the city government should take into account all available modes of public transportation and may be utilized by the city community. The design of vehicles that will be used as public transportation must also be adapted to the needs of the community and conditions in urban areas.